Corporate Policies and Practices among Contingent Workers in Private Retail Stores: Basis for Intervention Measures - Rachel Ann Q. Capacite; Jeffrey G. Capacite (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explores the complex landscape of business policies and practices relating to contingent labor in the setting of independent retail stores. The workforce in the retail sector is largely made up of contingent workers, who frequently include temporary, part-time, seasonal, and contract employees. Due to the needs of contemporary techniques like just-in-time production as well as seasonal and cyclical dynamics, contingent contracts enable some businesses to maximize employee flexibility. They regrettably frequently earn less money and receive less benefits than regular full-time or